Videos for Fig. 15 with a small and a large laser beam diameter, respectively - Wang, Chong; Suder, Wojciech; Ding, Jialuo; Williams, Stewart (Cranfield University, 2021)
These are two supplementary videos for Fig 15, showing deposition process with two different laser beam diameters (12 mm and 2 mm, respectively) in wire based PTA-laser hybrid additive manufacture.
Keywords: Wire based additive manufacture; Bead shape; PTA-laser hybrid additive manufacture; Additive Manufacturing